2010
DOI: 10.1002/aenm.201000030
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Role of Processing and Morphology in Determining Degradation Rates in Polymer Solar Cells

Abstract: With rapid increase in the efficiencies of polymer solar cells (PSCs) in the last few years, the issue of device stability is taking center stage in organic photovoltaic research. In this work, the effects of oxygen and light on the degradation of charge‐transport properties of the bulk polymer active layer are studied over short timescales. It is shown that although different processing techniques produce similar efficiencies for pristine devices, they result in different degradation rates. This variation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 45 publications
1
27
0
Order By: Relevance
“…[117] The influence of different processing parameters on the morphological stability have been studied by Kumar et al who found that P3HT:PCBM films spin-coated with added 1,8-octanedithiol degraded much faster than films made from other solvents. [118] The temperature used to dry the active layer film may also affect both efficiency and stability as shown by Lin et al [119] If the active layer film is dried at -5 °C compared to RT the efficiency increased from 3.23 to 4.70% and a storage half-life increased from 143 h to 1250 h. Also the regio-regularity of the P3HT seems to have a large effect. In a study with two regio-regularities of 94% and 98% Ebadian et al showed that the devices based on the high regio-regular P3HT lost efficiency much faster than those based on the low regio-regular material.…”
Section: The Active Layermentioning
confidence: 93%
“…[117] The influence of different processing parameters on the morphological stability have been studied by Kumar et al who found that P3HT:PCBM films spin-coated with added 1,8-octanedithiol degraded much faster than films made from other solvents. [118] The temperature used to dry the active layer film may also affect both efficiency and stability as shown by Lin et al [119] If the active layer film is dried at -5 °C compared to RT the efficiency increased from 3.23 to 4.70% and a storage half-life increased from 143 h to 1250 h. Also the regio-regularity of the P3HT seems to have a large effect. In a study with two regio-regularities of 94% and 98% Ebadian et al showed that the devices based on the high regio-regular P3HT lost efficiency much faster than those based on the low regio-regular material.…”
Section: The Active Layermentioning
confidence: 93%
“…In some organic photovoltaic (OPV) devices, thermal annealing is an important approach to tune the nanoscale morphology of the active layer to improve device efficiency . This is commonly observed in OPVs made of semi‐crystalline conjugated polymers as electron donors, for example, P3HT, poly(2,5‐bis(3‐tetradecylthiophen‐2‐yl)thieno[3,2‐b] thiophene) (PBTTT) and so on .…”
Section: Surface and Interface Modified Thermal Properties In Polymermentioning
confidence: 99%
“…The factors limiting stability of OSCs include light, oxygen, and humidity . By encapsulation, the effect of oxygen and humidity could be mostly suppressed while the unavoidable light and accumulated heat from illumination may degrade the performance seriously .…”
Section: Introductionmentioning
confidence: 99%